The Effect of Information Technology, Single Sign on Information System, Knowledge Management on Business Performance (Literature Review Executive Support System for Business) - Zuleha, Arisnani (Dinasti Publisher, 2022)
The Executive Support System (ESS) is software that allows its users to convert data owned by the company into reports at the executive level that can be quickly accessed for various uses by various parts or work units within the company. ESS is also known by another term as Executive Information System (EIS). EIS is a system based on information technology support intended to assist company executives in the decision making process. Therefore ESS or EIS is a supporting system for executive decision making processes. In the results of this literature review obtained regarding factors that can affect business performance within the company. These factors include: (1) Information Technology has an effect on Business Performance (2) Single Sign on Information Systems has an effect on Business Performance (3) Knowledge Management has an effect on Business Performance.